К изучению дендролеляпин Северной Америки (Multidendrolaelaps, Rhodacaridae, Gamasina) - Щербак, Г.И. (Вестник зоологии, 1985)
Multidendrolaelaps trispinosus sp. n. is similar to M. ulmi, females, males and nymphs of the new species sharply differ in the presence, apart of Pl₄, incrassed M₉ and Pl₅. M. inconstans sp. n. is similar to M. tetraspinosus, males and females differ in smaller size, shorter peritremes, females-in ventro-anal shield shape, shorter and wider, weakly sclerotized tubular part of seminal receptaculum, males-in short spermodactylus. M. harlbutti sp. n.- females similar to M. isodentatus, clearly differ in ventro-anal shield shape. Ionger D₈ (2✕D₂) and S₆ (reach the half length of S₆), M₉ and Pl₅. M. epistospinosus sp. n.- mostly similar to M. euepistomus and M. euepistosimilis, differ from both males and females of the new species in longer hypostomal row and longer S₈, from M. euepistomus-in longer peritremes, lower teeth number on movable cheliceral finger in female, spermoductyle shape and presence of fusiform S₇ in male, from males of M. euepistosimilis-in longer D₈ and S₆, large medial tectum projection, punctuated cuticle in the area of humeral chetae and in anterior angles of hind shield and in absence of that between chetae D₆-D₇. M. spinosus elongatus females differ from those of nominate subspecies in elongated body shape, longer anterior shield, relatively longer D₈, ventro-anal shield shape. Type material is deposited in Biosystematics Research Institute, Ottawa, Canada. The reason is suggested to unite subgenera Epistodendrolaelaps and Multidendrolaelaps into a distinct genus, its diagnosis is improved by a number of characters.